The attitude of healthcare professionals plays an important role in the uptake of diabetes self‐management education: analysis of the Barriers to Uptake of Type 1 Diabetes Education (BUD1E) study survey. Issue 9 (25th June 2018) - Harris, S. M.; Joyce, H.; Miller, A.; Connor, C.; Amiel, S. A.; Mulnier, H.
Abstract: Aim: To explore reasons for the poor uptake of accredited diabetes self‐management education (DSME) in adults with Type 1 diabetes. Methods: The study was set in an urban population in South London, UK. A cross sectional survey gathered demographic, diabetes service‐use data, psychological scores and reasons for non‐attendance at locally‐available DSME. In addition, 56 healthcare professionals were surveyed. Results: Responses to surveys were returned by 496 adults with Type 1 diabetes (33% response rate), of whom 263 had attended DSME (53%). Multivariable analysis adjusted for significant variables identified four key variables influencing attendance. Non‐attendance was associated with men (OR 0.55 CI 0.37‐0.84, p = 0.005), lower educational attainment (OR 0.45 CI 0.28‐0.73, p = 0.001), higher glycated haemoglobin (OR 1.74 CI 1.03‐2.94, p = 0.04) and healthcare professional encouragement to attend (OR 1.7 CI 1.28‐2.3, p = 0.001). The most frequently reported barriers to attendance were work (37%) and time (14%) commitments. Only 49% of healthcare professionals (HCPs) correctly identified the most likely barriers. Those HCPs who had observed courses believed more in their efficacy, with higher uptake within their clinic population. Conclusions: Social determinants of health, particularly educational attainment and gender, increase health inequalities by influencing decisions to attend evidence‐based education courses. Healthcare professional communication is paramount to encourage attendance, and observation of a course may facilitate this. What's new?: This is the first survey study to investigate reasons for the poor uptake of diabetes self‐management education in Type 1 diabetes. Four key variables were found to influence attendance: gender, glycaemic control, educational attainment and healthcare professional message. A positive healthcare professional message about diabetes self‐management education courses is essential for attendance. This study highlights populations being underserved by the current provision of diabetes self‐management education and potential targets to improve uptake.